The Relationship of Breast Cancer with Age in Bangladeshi Female Breast Cancer Patients (Bangladesh Journal of Anatomy, 2018)
Context: Breast cancer is a multi-factorial disease and consistently ranks as one of the top killer cancers in women. The increasing incidence of breast cancer prevailing in Bangladeshi women, especially at a younger age, and their survival rate justifies research on breast cancer epidemiology. Age is the established risk factor for breast cancer. Therefore, the objective of this study was to determine the relationship of breast cancer with age. Materials & Methods: A cross-sectional study was done on 100 adult Bengali Bangladeshi female patients with ductal cell carcinoma of breast of 25 to 70 years of age group. The study was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from March 2017 to February 2018.Semi-structured data collection sheet was used to collect the age of the patients and the age of onset of cancer. Results: The mean age of the patients was 45.55 years, and the onset of cancer was predominantly below 50 years of age. Conclusion: This study findings may contribute significantly to current knowledge of risk factors for breast cancer and help to identify women who need benefit most from screening or other preventive measures.Bangladesh Journal of Anatomy July 2018, Vol. 16, No. 2, pp. 38-42